Pulmonary vascular disease associated with schistosomiasis. Issue 12 (December 2010) - Kolosionek, Ewa; Crosby, Alexi; Harhay, Michael O; Morrell, Nicholas; Butrous, Ghazwan
In this article we focus on the pathogenesis and clinical characteristics of schistosomiasis infection on the lung vasculature. Overall, the basic biology and understanding of Schistosoma immune responses and their effect on the cardiopulmonary system is limited in both animal and human models, which hinders clinical care and drug development. The inflammatory response to the eggs in the lung appears to contribute to the remodeling of the pulmonary vessels. Portal hypertension caused by parasitemia also appears to contribute to the development of pathophysiologic alterations of the pulmonary vascular bed. Antischistosomal therapy, praziquantel, used for pulmonary hypertension secondary to schistosomiasis usually has no effect, but it is given to prevent further progression of disease. Currently, there are no clinical trials for the treatment of pulmonary vascular disease secondary to schistosomiasis. Specialty drugs such as phosphodiesterase type 5 or tyrosine kinase inhibitors exhibit some interesting activity, yet are prohibitively expensive, lack safety and efficacy studies in schistosomiasis endemic populations, and tend to be limited by safety, efficacy, route of administration and compliance problems.